Warunki udziału w postępowaniu o udzielenie zamówienia publicznego jako przejaw zapobiegania patologii w obrocie gospodarczym - Gola, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Contact between the sphere of the civil service and the private sphere creates a potential risk of the occurrence of pathologies manifesting chiefly in attempts at influencing individuals holding public posts. Proper management of public property in the process of awarding contracts is possible only through definition of terms for participation in proceedings. There is therefore no doubt that the institution of contractor exclusion may be counted among the instruments for prevention of pathologies in economic activity. The legislator has provided for powers for the awarding entity thanks to which it is able to exclude some contractors from proceedings. The purpose of the solutions discussed in the article is ensuring the participation in proceedings of those contractors which are best and are credible, and which present good and honest bids
Keywords: korupcja; zamówienia publiczne